Comparative Analysis of Non-Performing Loans and Cost Efficiency: Evidence from Hong Kong Banking - BINGHAN, LING (2017)
Hong Kong is one of the international financial centre in the world and its banking industry is an important part of its financial industry. However, the credit quality in Hong Kong banking system had a relatively slight fluctuation in the past few years. Therefore, it is necessary to understand and assess bank efficiency and bank credit risk and thus contribute to the profitability and the future development of Hong Kong banking. This paper will examine the determinations of banks efficiency and credit risk and then further explore that the relationship of both based on past 6-year Hong Kong banks data, separately for three categories, China owned banks, Hong Kong owned banks and foreign owned banks. Stochastic Frontier Analysis (SFA) will be applied to evaluate bank cost efficiency and Generalized Method of Moments (GMM) approach will be adopted for as a dynamic panel data estimator to estimate the determinants of non-performing loans which based on the hypotheses. The results show that, Hong Kong owned banks and foreign owned banks present a much higher cost efficiency than China owned banks. In addition, macroeconomic factors have no significant effect on bank cost efficiency. But, macroeconomic variables have different degrees of impact on credit risk. Exchange rate had an effect on bank’ s credit risk and ‘Bad management’ hypothesis was verified in China owned banks. Complicated internal banking systems may promote to a stringent loan review system, but may also be one of the reasons for cost inefficiencies. Hong Kong local banks presented the highest level of cost efficiency. However, they might rely on their localization and policy advantages and increase bank exposure with the selection of high riskiness loans and causes a higher level of credit risk and non-performing loans. With regards to foreign owned banks in Hong Kong, no significant listed hypothesis can be employed. But foreign bank could improve cost efficiency in view of individual difference and carry out business along the economy business. In summary, greater market openness, more robust risk management mechanism, more complete cost management system, as well as more sensitive to the market and the macroeconomic might be four dimensions for a more efficient banking industry and declining credit risk.